(untitled) - Moore, Keith L (Philadelphia, 1999)
The number one anatomy text for medical and allied health students, Clinically Oriented Anatomy features comprehensive coverage of anatomy along with clinical correlations provided by the famous blue boxes. New features in this edition include: completely new art program; surface anatomy and medical imaging boxes; and new illustrated tables. Clinically Oriented Anatomy, Fourth Edition is now packaged with a student version of Dynamic Human Anatomy , an interactive CD-ROM which includes 800 images from Grant's Atlas of Anatomy , Eleventh Edition, 8 video clips from Acland's DVD Atlas of Human Anatomy , and 100 USMLE-style review questions in anatomy.
Keywords: Human anatomy,Giải phẫu người